Enhancing Financial Inclusion and Financial Literacy for Small and Medium Enterprises (SMEs) in Zambia: Challenges, Opportunities and Strategies for Growth - Kuldip Paliwal (Indonesian Journal of Islamic Economics and Finance)
The study aims to assess the range of FI among SME managers. Financial Inclusion (FI) ensures that every individual, especially the marginalized, has adequate access to financial services. The main objective of this study is to analyze the extent of SME managers’ access to financial schemes and policies in Zambia, Africa. The study describes the budget provided by the Zambian government for SMEs, which will help in examining the level of financial literacy (FL) of SME managers regarding budgeting. Despite their potential, SMEs face many challenges, including limited access to finance, inadequate financial literacy among entrepreneurs, and a fragmented regulatory environment and identifies opportunities to improve financial inclusion through targeted strategies. The study emphasizes the need to enhance financial literacy programs tailored to the needs of SME owners to empower them. The study also highlights the importance of collaborative efforts between government agencies, financial institutions, and development partners to create an enabling ecosystem. The study proposes actionable strategies that Zambia can implement to improve access to finance and enhance financial literacy. The study findings show that most entrepreneurs agree that financial accessibility is important for SME development and implement inclusive policies to expand the reach of financial services.